Changes of Thymoquinone, Thymol, and Malondialdehyde Content of Black Cumin (Nigella sativa L.) in Response to Indonesia Tropical Altitude Variation - . Herlina; Sandra Arifin Aziz; Ani Kurniawati; Didah Nur Faridah (Bogor Agricultural University, Indonesia, 2017)
Black cumin cultivated in many subtropical regions in the world, including Asia, Middle East, and North Africa. The most active constituent of black cumin is thymoquinone representing 18.4%–24% of the volatile oil and thymol. Data about thymoquinone and thymol came from the country of origin, but no data from tropical region. This study aimed to analyze the production of chlorophyll, thymoquinone, thymol, and malondialdehyde from black cumin cultivated at three altitudes of Indonesian tropical region. The result showed that Kuwait accession cultivated at middle altitude contains the highest levels of thymoquinone (2940.43 mg/kg), and the highest levels of thymol were found in India accession cultivated at high altitude (141.46 mg/kg). Data showed that the level of malondialdehyde at low (220 meter above sea level [masl]) and middle (560 masl) altitudes is higher than high (1.280 masl) altitude.